Strategi Guru dalam Mengelola Pembelajaran Bagi Siswa dengan ASD (Kategori Sedang) di Lingkungan Sekolah Inklusi Surakarta - Ganesha Syalom Lintang Panggayuh (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to examine teachers strategies in managing learning for students with Autism Spectrum Disorder (ASD) in the moderate category at inclusive schools in surakarta. This research employed a descriptive qualitative approach with data collection techniques through observation and interviews with special education teachers. The results revealed that teachers implemented various strategies, including differentiated instruction, the use of visual media, positive reinforcement, and individual assistance to meet the learning needs of student with ASD. However, several challenges were encountered, such as limited specific training for teachers, inadequate supporting facilities, and difficulties in handling the distinctive behaviors of student with ASD. Supporting factors included inclusive school policies, active parental involvement, and collaboration among teachers, schools, families, and professionals play a crucial role in the successful management of learning for student with moderate ASD in inclusive school settings.